Death Sentence for Perpetrators of Criminal Acts of Corruption in Indonesia - Ahmad, Kamri; Hatta, Muhammad; Kahar, Muhammad Syahrul; Kadir, Yusrianto; Kadir, Muhammad Arifin Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is one of the countries that still applies the death penalty. In Article 2 Paragraph (2) of Law No. 31 of 1999 Jo. Law No. 20 of 2001 concerning Eradication of Corruption Crimes determines that the application of the death penalty is still limited and has certain criteria. One of the criteria for the implementation of the death penalty is corruption against the authority to overcome national natural disasters, widespread social unrest, monetary crisis, and tackling corruption. However, the authors are of the view that these criteria are very difficult to apply and give rise to multiple interpretations on the applicative level. Therefore, the formulation of the criteria for imposing capital punishment on perpetrators of corruption must be practical so that law enforcers easily apply the death penalty to perpetrators of corruption in Indonesia.